2016
DOI: 10.1128/msphere.00009-15
|View full text |Cite
|
Sign up to set email alerts
|

Viral Determinants of miR-122-Independent Hepatitis C Virus Replication

Abstract: Hepatitis C virus (HCV) is the leading cause of liver cancer in the Western Hemisphere. HCV infection requires miR-122, which is expressed only in liver cells, and thus is one reason that replication of this virus occurs efficiently only in cells of hepatic origin. To understand how HCV genetics impact miR-122 usage, we knocked out miR-122 using clustered regularly interspaced short palindromic repeat (CRISPR) technology and adapted virus to replicate in the presence of noncognate miR-122 RNAs. In doing so, we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(44 citation statements)
references
References 35 publications
3
41
0
Order By: Relevance
“…More recently, HCV was shown to replicate independent of miR-122 (Hopcraft et al, 2016; Thibault et al, 2013), and specific mutations in the HCV 5′ UTR not only facilitate HCV gene expression when miR-122 abundance is decreased but also in the absence of miR-122 (Hopcraft et al, 2016; Israelow et al, 2014). Interestingly depletion of DDX6 affects both miR-122 dependent and independent HCV gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, HCV was shown to replicate independent of miR-122 (Hopcraft et al, 2016; Thibault et al, 2013), and specific mutations in the HCV 5′ UTR not only facilitate HCV gene expression when miR-122 abundance is decreased but also in the absence of miR-122 (Hopcraft et al, 2016; Israelow et al, 2014). Interestingly depletion of DDX6 affects both miR-122 dependent and independent HCV gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The identity of the Huh7 and Huh7.5 cell lines was verified using the Promega GenePrint STR kit (DNA Analysis Facility, Duke University), and cells were verified as mycoplasma free by the LookOut Mycoplasma PCR detection kit (Sigma). Huh7.5 CD81 KO cells were generated by CRISPR, as described before, with details given in the Supplemental Experimental Procedures (Hopcraft et al, 2016; Hopcraft and Evans, 2015). …”
Section: Methodsmentioning
confidence: 99%
“…Approaching this point, a function of miR-122 in replication was proposed that could stimulate HCV RNA synthesis by altering the balance of viral RNAs engaged in replication versus translation ( Masaki et al, 2015 ). Moreover, it has been shown that revertants in the 5′ UTR miR-122 binding sites that do not support miR-122 binding can be stable ( Hopcraft et al, 2016 ), even suggesting a miR-122-independent role of the primary sequence of the respective HCV 5′ UTR region in the HCV life cycle. On the other hand, an decrease in cellular miR-122 concentration lead to the emergence of a mutation in the HCV sequence that slightly increased the affinity of miR-122 binding, indicating a certain need for miR-122 in efficient HCV replication ( Israelow et al, 2014 ).…”
Section: The Liver-specific Microrna-122mentioning
confidence: 99%